The Effects of Full and Alternative Day Block Scheduling on Language Arts and Science Achievement in a Junior High School - Lewis, Chance W.; Cobb, R. Brian (Education Policy Analysis Archives, 2003)
The effects of a full (4 X 4) block scheduling program and an alternate day (AB) block scheduling program in a junior high school were under investigation in this study through the use of an ex post facto, matched sampling design. Measures investigated were standardized achievement tests in science and language arts. Both forms of block scheduling had been in place for several years, and one teacher in science and one teacher in language arts had taught students under both forms of scheduling. Because the sampling designs and analyses were different for the science and the language arts areas, two studies are reported here—each examining the effects of 4 x 4, AB, and traditional scheduling with attribute variables of gender and student skill levels in each analysis. Results consistently show students in both forms of block scheduling outperforming students in traditional scheduling, and that AB block scheduling has the largest positive impact on low-achieving students.